Исследования адсорбции технеция-99м на γ-оксидах алюминия с различной кислотной активацией - Скуридин В. С. Виктор Сергеевич; Стасюк Е. С. Елена Сергеевна; Нестеров Е. А. Евгений Александрович; Садкин В. Л. Владимир Леонидович; Рогов А. С. Александр Сергеевич; Варламова Н. В. Наталья Валерьевна (2013, 2013)
В фонде НТБ ТПУ отсутствует